Ultimate strength performance of Northern sea going non-ice class commercial ships - Park, D.K. (Techno-Press, 2014)
In the early design stage of ships, the two most important structural analyses are performed to identify the structural capacity and safety. The first step is called global strength analysis (longitudinal strength analysis or hull girder strength analysis)and the second step is local buckling analysis (stiffened panel strength analysis). This paper deals with the ultimate strength performance of Arctic Sea Route-going commercial ships considering the effect of low temperature. In this study, two types of structural analyses are performed in Arctic sea conditions. Three types of ship namely oil tanker, bulk carrier and container ship with four different sizes (in total 12 vessels) are tested in four low temperatures (-20, -40, -60 and -80°C), which are basedon the Arctic environment and room temperature (20°C). The ultimate strength performance is analysed with ALPS/HULL progressive hull collapse analysis code for ship hulls, then ALPS/ULSAP supersize finite element method for stiffened panels. The obtained results are summarised in terms of temperature, vessel type, vessel size, loading type and other effects. The important insights and outcomes are documented. Copyright © 2014 Techno-Press, Ltd.